Ablation of the presynaptic organizer Bassoon in excitatory neurons retards dentate gyrus maturation and enhances learning performance - Annamneedi, Anil; Caliskan, Guersel; Mueller, Sabrina; Montag, Dirk; Budinger, Eike; Angenstein, Frank; Fejtová, Anna; Tischmeyer, Wolfgang; Gundelfinger, Eckart D.; Stork, Oliver (Brain Structure & Function, 2018)
Bassoon is a large scaffolding protein of the presynaptic active zone involved in the development of presynaptic terminals and in the regulation of neurotransmitter release at both excitatory and inhibitory brain synapses. Mice with constitutive ablation of the Bassoon (Bsn) gene display impaired presynaptic function, show sensory deficits and develop severe seizures. To specifically study the role of Bassoon at excitatory forebrain synapses and its relevance for control of behavior, we generated conditional knockout (Bsn cKO) mice by gene ablation through an Emx1 promoter-driven Cre recombinase. In these animals, we confirm selective loss of Bassoon from glutamatergic neurons of the forebrain. Behavioral assessment revealed that, in comparison to wild-type littermates, Bsn cKO mice display selectively enhanced contextual fear memory and increased novelty preference in a spatial discrimination/pattern separation task. These changes are accompanied by an augmentation of baseline synaptic transmission at medial perforant path to dentate gyrus (DG) synapses, as indicated by increased ratios of field excitatory postsynaptic potential slope to fiber volley amplitude. At the structural level, an increased complexity of apical dendrites of DG granule cells can be detected in Bsn cKO mice. In addition, alterations in the expression of cellular maturation markers and a lack of age-dependent decrease in excitability between juvenile and adult Bsn cKO mice are observed. Our data suggest that expression of Bassoon in excitatory forebrain neurons is required for the normal maturation of the DG and important for spatial and contextual memory.
EVALuna2:211603